LCR testing for gonorrhoea and chlamydia in population surveys and other screenings of low prevalence populations: coping with decreased positive predictive value. Issue 2 (1st April 2003) - Zenilman, J M; Miller, W C; Gaydos, C; Rogers, S M; Turner, C F
Abstract : Objective: Nucleic acid amplification tests have facilitated field based STD studies and increased screening activities. However, even with highly specific tests, the positive predictive value (PPV) of such tests may be lower than desirable in low prevalence populations. We estimated PPVs for a single LCR test in a population survey in which positive specimens were retested. Methods: The Baltimore STD and Behavior Survey (BSBS) was a population based behavioural survey of adults which included collecting urine specimens to assess the prevalence of gonorrhoea and chlamydial infection. Gonorrhoea and chlamydial infection were diagnosed by ligase chain reaction (LCR). Nearly all positive results were retested by LCR. Because of cost considerations, negative results were not confirmed. Predicted curves for the PPV were calculated for a single testing assuming an LCR test sensitivity of 95%, and test specificities in the range 95.0%–99.9%, for disease prevalences between 1% and 10%. Positive specimens were retested to derive empirical estimates of the PPV of a positive result on a single LCR test. Results: 579 participants age 18–35 provided urine specimens. 20 (3.5%) subjects initially tested positive for chlamydial infection, and 39 (6.7%) tested positive for gonococcal infection. If positive results on the repeat LCR are taken as confirmation of a "true" infection, the observed PPV for the first LCR testing was 89.5% for chlamydial infection and 83.3% for gonorrhoea. This is within the range of theoretical PPVs calculated from the assumed sensitivities and specificities of the LCR assays. Conclusions: Empirical performance of a single LCR testing approximated the theoretically predicted PPV in this field study. This result demonstrates the need to take account of the lower PPVs obtained when such tests are used in field studies or clinical screening of low prevalence populations. Repeat testing of specimens, preferably with a different assay (for example, polymerase chain reaction), and disclosure of the non-trivial potential for false positive test results would seem appropriate in all such studies.